Digital-based Political Education through the Election Care Village Program in Deli Serdang Regency - Kusmanto, Heri; Pardede, Piki Darma Kristian; Nasution, Faiz Albar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The General Election Commission of the Republic of Indonesia established Desa Peduli Pemilu dan Pemilihan (DP3) to increase knowledge skills and strengthen public acceptance and trust in the election mechanism as the main instrument of the political system. The low voter turnout in Deli Serdang Regency is the reason for the KPU of North Sumatra Province to focus the program on Bandar Khalipah Village and Tembung Village. Observation results show the usefulness of the Desa Peduli Pemilu dan Pemilihan program as a projection to increase voter participation in 2024. Therefore, this service activity was carried out to provide an understanding of Digital-Based Political Education through the Election and Election Care Village Programme in Deli Serdang Regency by involving Bandar Khalipah Village and Tembung Village. The method used is a combination of Participatory Rural Appraisal and Participatory Learning and Action through three stages, namely Preparation, Implementation, and Evaluation. Firstly, this service activity was carried out together with DP3 with Bandar Khalipah Village and Tembung Village, which included learning about political education. Second, increasing understanding of the development of socialization and political education for citizens and increasing voter participation in Deli Serdang Regency; and third, assisting in digital content creation training. The results of this service recommend that activity participants be able to transform the understanding of political education to increase voter participation in Deli Serdang Regency. This service also suggests that the coaching and mentoring of digital content creation training be used in the long term by Bandar Khalipah Village and Tembung Village.